MOCAfest (Marketplace of Creative Arts) - Rafee, Y.M (2017)
MOCAfest (Marketplace of Creative Arts), the WIEF Foundation’s arts and culture festival, used the platform to showcase emerging creative artists from around the world and display their works. The main lobby of the WIEF hosted MOCAfest’s visual art exhibition and live installations. The forum also showcased a MOCAsouq, a creative bazaar for all things artisanal.